The implementation of domiciliary dental care from a university hospital: A retrospective review of the patients and performed treatments in central Taiwan from 2010 to 2020 - Chuan-Hang Yu; Yu-Hsun Wang; Yu-Hsien Lee; Yu-Chao Chang (Elsevier, 2022)
Background/purpose: People who suffer with chronic illness, functional impairment, or cognitive impairment are not easily to visit dental clinics. Domiciliary dental care (DDC) can provide the feasible alternative for these clients. In this study, we first reported the DDC services from a university hospital in central Taiwan from 2010 to 2020. Materials and methods: This retrospective study collected the DDC data from Department of Dentistry, Chung Shan Medical University Hospital, Taichung, Taiwan. The data including age, sex, geographic locations, place of residence, grade of disability, and type of dental treatment for the patients were obtained and analyzed. Results: A total of 419 patients (168 females and 251 males) who received dental treatment were included in the study. The average age was 57.4 years old. The total DDC services were up to 2444 visits. The top of place of residence for DDC is patient's home (231/419; 55.13%). Scaling was the most common type of dental treatment for DDC (317/419; 75.67%). The male patients whose age <60 years old had received more DDC (p = 0.002). The profound grade of disability had higher DDC in age <60 years old group (p < 0.001). Conclusion: Taken together, this study demonstrates the demographic data of DDC in central Taiwan. The results may be valuable for governmental policy to improve the availability of DDC and in turn to facilitate oral health in this specific group of dental patients.